Subgrouping patients with zoster-associated pain according to sensory symptom profiles: A cluster analysis - Kim, Hee Jung; Yoon, Kyung Bong; Kang, Misun; Yang, Yun Seok; Kim, Shin Hyung (Frontiers in Neurology, 2023)
Background and goal of study Patients with zoster-associated pain exhibit a variety of sensory symptoms and forms of pain and complain of different pain patterns. The purpose of this study is to subgroup patients with zoster-associated pain who visited a hospital using painDETECT sensory symptom scores, analyze their respective characteristics and pain-related data, and compare similarities and differences among the groups. Materials and methods The characteristics of 1,050 patients complaining of zoster-associated pain and pain-related data were reviewed retrospectively. To identify subgroups of patients with zoster-associated pain according to sensory symptom profiles, a hierarchical cluster analysis was performed based on the responses to a painDETECT questionnaire. Demographics and pain-related data were compared among all subgroups. Results and discussion Patients with zoster-associated pain were classified into 5 subgroups according to the distribution of sensory profiles, with each subgroup exhibiting distinct differences in the expression of sensory symptoms. Patients in cluster 1 complained of burning sensations, allodynia, and thermal sensitivity, but felt numbness less strongly. Cluster 2 and 3 patients complained of burning sensations and electric shock-like pain, respectively. Cluster 4 patients complained of most sensory symptoms at similar intensities and reported relatively strong prickling pain. Cluster 5 patients suffered from both burning and shock-like pains. Patient ages and the prevalence of cardiovascular disease were significantly lower in cluster 1. Patients in clusters 1 and 4 reported longer pain duration compared with those in clusters 2 and 3. However, no significant differences were found with respect to sex, body mass index, diabetes mellitus, mental health problems, and sleep disturbance. Pain scores, distribution of dermatomes and gabapentinoid use were also similar among the groups. Conclusions Five different subgroups of patients with zoster-associated pain were identified on the basis of sensory symptoms. A subgroup of younger patients with longer pain duration showed specific and distinct symptoms, such as burning sensations and allodynia. Unlike patients with acute or subacute pain, patients with chronic pain were associated with diverse sensory symptom profiles.